Review on Development of reliable drinking water source and/or augmentation of existing source to provide long term sustainability of water supply system. (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Access to safe and reliable drinking water is a fundamental human right and a cornerstone ofsustainable development. This review paper critically examines the development of reliable drinkingwater sources and the augmentation of existing sources to ensure the long-term sustainability of watersupply systems. With a growing global population and increasing environmental pressures, the demandfor clean and dependable water resources has never been more pressing. This comprehensive reviewassesses the various strategies, technologies, and approaches employed worldwide to address this vitalchallenge. We delve into the innovative solutions, such as groundwater recharge, desalination, waterrecycling, and watershed management, which are pivotal in enhancing the resilience of water supplysystems. Additionally, we explore the socio-economic and environmental implications of thesestrategies, emphasizing the importance of community engagement, equity, and ecological preservation.By synthesizing the latest research findings and case studies, this review aims to provide valuableinsights and guidance for policymakers, water resource managers, and researchers, with the ultimategoal of securing a sustainable and equitable water future for all.